2019
DOI: 10.3390/ijerph16050887
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Metal Content of Waste Mobile Phones and Estimation of Their Recovery Potential in Turkey

Abstract: Waste mobile phones constitute one of the fastest growing Waste Electrical and Electronic Equipment (WEEE) types all over the world due to technological innovations and shortening of their life span. They contain a complex mix of various materials, such as basic metals, precious metals and rare earth elements and represent an important secondary raw metal source. The main objectives of this study were to characterize the metal concentration of waste mobile phones by optimizing the inductively coupled plasma op… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 44 publications
0
43
1
Order By: Relevance
“…We included Incandescent Bulb (IB), Compact Fluorescent Lighting (CFL), Light Emitting Diode (LED) Bulb, Mobile Phone (MP), Desktop Computer (DC), Laptop Computer (LC), Liquid Crystal Display (LCD) Monitor, CRT TV, Plasma Display Panel (PDP) TV, LCD TV, Washing Machine (WM), Refrigerator (RF), Air Conditioner (AC). We also included 14 electronic components, namely, Lithium Battery (LB), Hard Disk Drive (HDD), Solid State Drive (SSD), LCD, Organic Light-emitting Diode (OLED) display, MP WPCB, DC WPCB, LC WPCB, CRT TV WPCB, PDP TV WPCB, LCD TV WPCB, WM WPCB, RF WPCB, and AC WPCB (Bahaloo-Horeh et al, 2018;Buechler et al, 2020;Chen et al, 2016;Cucchiella et al, 2015;Kang et al, 2013;Keith et al, 2008;Kim et al, 2019;Minxi Wang, 2018;Oguchi et al, 2011Oguchi et al, , 2013Priya and Hait, 2018a, b;Qi et al, 2020;Sahan et al, 2019;Yamane et al, 2011;Yeom et al, 2018). To compare different WEEE and components, we focused on data for metals because organic pollutants were not uniformly investigated across the two categories.…”
Section: Metal Contents For Weee and Components By Collectionmentioning
confidence: 99%
“…We included Incandescent Bulb (IB), Compact Fluorescent Lighting (CFL), Light Emitting Diode (LED) Bulb, Mobile Phone (MP), Desktop Computer (DC), Laptop Computer (LC), Liquid Crystal Display (LCD) Monitor, CRT TV, Plasma Display Panel (PDP) TV, LCD TV, Washing Machine (WM), Refrigerator (RF), Air Conditioner (AC). We also included 14 electronic components, namely, Lithium Battery (LB), Hard Disk Drive (HDD), Solid State Drive (SSD), LCD, Organic Light-emitting Diode (OLED) display, MP WPCB, DC WPCB, LC WPCB, CRT TV WPCB, PDP TV WPCB, LCD TV WPCB, WM WPCB, RF WPCB, and AC WPCB (Bahaloo-Horeh et al, 2018;Buechler et al, 2020;Chen et al, 2016;Cucchiella et al, 2015;Kang et al, 2013;Keith et al, 2008;Kim et al, 2019;Minxi Wang, 2018;Oguchi et al, 2011Oguchi et al, , 2013Priya and Hait, 2018a, b;Qi et al, 2020;Sahan et al, 2019;Yamane et al, 2011;Yeom et al, 2018). To compare different WEEE and components, we focused on data for metals because organic pollutants were not uniformly investigated across the two categories.…”
Section: Metal Contents For Weee and Components By Collectionmentioning
confidence: 99%
“…All reagents were purchased from commercial sources and used as received. 1 H and 13 C NMR were recorded at room temperature on Bruker © Advance spectrometers and all chemical shift values were referenced to an internal standard of tetramethylsilane (δ = 0.0 ppm). Fourier transform infra-red (FTIR) spectra were recorded on Bruker © Alpha Platinum-Attenuated Total Reflectance IR spectrometer.…”
Section: Materials and Instrumentationmentioning
confidence: 99%
“… Liu et al (2019) concluded that non-PCB components of waste mobile phones account for more than 50% of the total economic value in terms of the recovery potential. Sahan et al (2019) estimated that the economic value of nearly 1.72 million USD and 37.6 million USD could be generated from recycling basic metals and precious metals in PCBs. Li et al (2020) utilized the minimum distance maximum receiving (MDMR) algorithm and reported that more than 400 million units of waste mobile phones could be recycled in China.…”
Section: Introductionmentioning
confidence: 99%